Characteristics of Injectable Contraceptive Users among Rural Women of a Selected Area of Bangladesh - Begum, N; Rahman, M; Afroz, S; Rahman, MM; Jabbar, MA (Northern International Medical College Journal, 2013)
DOI: http://dx.doi.org/10.3329/nimcj.v4i2.15834 Northern International Medical College Journal Vol.4(2) 2013: 269-272